SolidWorks. Компьютерное моделирование в инженерной практике - Алямовский А. А. Андрей Александрович; Собачкин А. А. Александр Александрович; Одинцов Е. В. Евгений Владимирович; Харитонович А. И. Алексей Игоревич; Пономарев Н. Б. Николай Борисович (Мастер)
Авт. указаны на обороте тит. л.